Prevention and Treatment of Cardiometabolic Diseases in Children with Overweight and Obesity: The Future of Healthcare - Valeria Calcaterra; Gianvincenzo Zuccotti (MDPI AG, 2022)
In this Special Issue we will consider the impact of obesity on health in order to review the latest findings on the risk factors associated with cardiometabolic diseases in children with overweight and obesity as well as to explore the pathogenic mechanisms and potential therapeutic targets. The role of weight-management strategies, including exercise, dietary changes and nutritional education, in preventing obesity-related complications will be considered. The improvement of many obesity-associated complications following bariatric surgery will also be reported. The timely implementation of preventive strategies in pediatric patients with overweight and obesity may ameliorate the future burden of weight-related diseases and the future of healthcare.